The Influence of Imagery Training Methods on Pointing Accuracy Results in Petanque Athletes - Abdullah, Abdullah; Samsudin, Samsudin; Nasrullah, Nasrullah; Mulyadi, Mulyadi; Irawan, Ewan (Yayasan Insan Mulia Bima, 2024)
The aim of this study is to know the influence of imagery training methods on the accuracy pointing results on petanque athletes STKIP Taman Siswa Bima. This study is an experimental study with the design of the research is